Normal tissue architecture determines the evolutionary course of cancer - Jeffrey West (Nature Portfolio, 2021)
Some cancers occur in spatially constrained tissues such as the mammary gland, and how the morphological features influence the evolution of the cancer is unclear. Here, the authors use mathematical modeling to study the question of competition for space and provide inferences on the mode of evolution of cancers in such tissues.